Nest-building performance in rats: impact of vendor, experience, and sex. (February 2020) - Schwabe, Kerstin; Boldt, Lena; Bleich, André; van Dijk, Roelof Maarten; Helgers, Simeon Oscar Arnulfo; Häger, Christine; Nowakowska, Marta; Riedesel, Ann-Kristin; Schönhoff, Katharina; Struve, Birgitta; Wittek, Jürgen; Potschka, Heidrun
Nest building behavior has been intensely applied as a parameter for severity assessment in mice. In contrast, only a limited number of studies have reported nest building data from rats. Here, we assessed nest building in rats in two different facilities addressing the hypotheses that the vendor, previous experience with the nesting material as well as sex of the rats has an impact on the performance. Data from two study sites and three raters were compared to obtain information about the robustness of nest complexity scoring. The findings demonstrate a generally poor nest building performance in rats with a pronounced day-to-day fluctuation, and site-specific differences. Application of a newly developed scoring system resulted in an intermediate inter-rater reliability. Previous experience with the nesting material did not exert a consistent impact on nest complexity scores. Sex differences proved to depend on vendor and animal facility without consistent findings supporting a superior performance in female or male rats. In conclusion, our findings argue against a robust and consistent influence of sex and familiarity with the nesting material. The comparison between facilities suggests that local conditions need to be considered as influencing factors, which should be explored in more detail by future multicenter approaches. Considering the day-to-day fluctuation and the intermediate inter-rater reliability, we highly recommend to base nest complexity evaluation on means from several subsequent days analyzed by a group of experienced raters.